Water mites delineating the Oriental and Palaearctic regions—the unique fauna of southern Iran, with description of one new genus, one new subgenus and 14 new species (Acari: Hydrachnidia) - Pešić, Vladimir; Smit, Harry; Saboori, Alireza (Zootaxa, 2012)
This paper deals with a collection of epigean and hypogean water mites from the Hormozgan and Sistan va Baluchestan prov-inces in southern Iran. One new genus, Haloaxonopsis, is described, characterized by the presence of so-called wheel-likeacetabula, a unique character so far known only in marine mites of the family Pontarachnidae. One new subgenus, Halolimne-sia, and fourteen new species are described: Hydrachna sistanica, Nilotonia hormozgana, Torrenticola asadiae, T. hormozgan-ensis, Monatractides martini, Neoatractides calidus, Limnesia diversipes, Atractides hormozganus, Javalbia persica,Axonopsis gloeeri, A. interstitialis, A. hyporheica, Haloaxonopsis salina and Albia hyporheica. The first descriptions of thefemale are given for Neumania cf. maharashtris Cook, 1967 and Arrenurus bharatensis Cook, 1967. The following species arereported for the first time in Iran: Hydrachna cf. vaillanti K. Viets 1951, H. globosa lacerata Lundblad, 1969, Diplodontus sil-vestrii (Daday, 1898), Hygrobates hamatus K. Viets, 1935, Atractides biscutatus Cook, 1967 and Arrenurus bharatensis Cook,1967. The zoogeographical and ecological characteristics of the water mite fauna of southern Iran are discussed. The fauna ofSE Iran is of Oriental character, and no typical Palaearctic species were found. Our study shows that this fauna is not transitional, suggesting a rather ‘sharp’ boundary between the Palaearctic and Oriental regions in southern Iran.